PENGARUH STATUS PEKERJAAN, KESEHATAN, DAN JUMLAH TANGGUNGAN KELUARGA TERHADAP PENGELUARAN KONSUMSI RUMAH TANGGA DI KOTA DENPASAR - Ariyani, Gusti Ayu Nyoman Dewi; Saskara, Ida Ayu Nyoman (E-Jurnal Ekonomi Pembangunan Universitas Udayana; Vol 12 No 11 (2023): Vol.12.No.11. NOVEMBER 2023, 2023)
This research was conducted with the aim of analyzing the effect of income, employment status, health, and number of family dependents on household consumption expenditures in Denpasar City either simultaneously or partially, as well as to determine the moderating effect of income and employment status on household consumption expenditures in Denpasar City. This research was conducted in Denpasar City. The choice of this location is because the City of Denpasar is the capital of the Province of Bali which is a Regency/City with the largest average monthly consumption per capita in the 2019-2021 period among other Regencies/Cities, however it fluctuates every year. The population used in this study were the heads of families in Denpasar City, namely 170,377 heads of families with a sample of 100 people. Taking the number of samples was determined using the proportional random sampling method. The analysis technique used is moderation regression analysis. The results of the analysis show that income has a positive and significant effect on consumption, employment status has a negative and significant effect on consumption, health has a positive and significant effect on consumption and the number of dependents has a positive and significant effect on consumption. Income can moderate employment status positively on consumption. keyword : Income, Employment Status, Health, Number of Dependent, Consumption spending